Cardiovascular collapse with attempted pericardial drain withdrawal - Molly B Kraus; Rachel A Spitznagel; Jane A Kugler (Wolters Kluwer Medknow Publications, 2016)
Cardiac tamponade is a rare but serious emergency condition in the pediatric population. As treatment, a pericardial drain is often placed to evacuate the fluid. We present a case of a 4-year-old girl with cardiac tamponade secondary to renal failure. After the tamponade resolved, she suffered cardiovascular collapse upon attempted drain withdrawal. This case highlights an unusual cause for cardiovascular collapse, which occurred on blind removal of a pericardial drain.